The Founders’ Panels from the Church of Saint Demetrius in Thessaloniki. The State of Portraiture in Early Byzantine Painting - Obraztsova, Ksenia B. (Actual Problems of Theory and History of Art, 2020)
The paper is dedicated to the founders’ panels from the church of Saint Demetrius in Thessaloniki.The representations of the historical figures are remarkable for the portrait-like appearance, unusual for the 7th century. The feature plays a crucial role for the identification of the anonymous images and at the same timemarks the difference between the depictions of saints and historical figures. To find a place of the ensemble within the fading tradition of portrait painting, the article is provided with a survey of major lines and means of transformation of the genre in various contexts throughout the Late Antique and Early Byzantine period. Stylization of the physiognomic features is regarded as one of the main tendencies of the development. The impact of it is ambiguous: on the one hand, stylization reveals the attitude towards the generalizing image, on the other it can be interpreted as a mean of emphasizing of individual characteristics. The latter peculiarity, in our view, binds the founders’ images with the much earlier portrait tradition and enables us to compare the 7th-century mosaics of Saint Demetrius with the sculpture portraits of late 4th — first half of the 5th century.This work is supported by the Russian Science Foundation under grant 20-18-00294 and performed in Scientific Research Institute of Theory and History of Architecture and Urban Planning, branch of the Central Institute for Research and Design of the Ministry of Construction and Housing and Communal Services ofthe Russian Federation.
Keywords: Early Christian art; Thessaloniki; portraiture; donor; Sant Demetrius